Gewetenloze kapitalisten, handige fiscalisten, strategische huisvaders of gedisciplineerde calvinisten? De Nederlandse Republiek als casestudy - Hart, M. 't (BMGN - Low Countries Historical Review, 2006)
J. Glete, War and the state in early modern Europe. Spain, the Dutch Republic and Sweden as fiscal-military states, 1500-1660 L. Greenfeld, The spirit of capitalism. Nationalism and economic growth Ph.S. Gorski, The disciplinary revolution. Calvinism and the rise of the state in early modern Europe J. Adams, The familial state. Ruling families and merchant capitalism in early modern Europe. Marjolein ’t Hart, Ruthless capitalists, skilful fiscalists, strategic fathers or disciplinedCalvinists? The Dutch Republic as a case studyThis article discusses four recent works by historical sociologists that use the Dutch Republic as a case-study in their comparative work. In studying large-scale processes such as state formation, economic growth and military development they highlight the importance of the interaction between central and local levels of government. The ‘bottom-up’ approach adopted by Adams (familial networks), Gorski (church disciplining), Greenfeld (orientation of entrepreneurs) and Glete (interests of local elites and organizations) is once again placed high of the research agenda. The Dutch Republic serves quite well as an interesting case from a comparative perspective.